Cumplimiento de Metas y Objetivos en el Departamento de Auditoría de la Hacienda Cooproclem - Mosquera Nazareno, Brando Jordano (2019)
Cooproclem, known to everyone as Hacienda La Clementina, is a farming production company that previously belonged to the Noboa Bananera Exporter, today the workers are the owners of the same being an approximate of 1,800 partners themselves who direct commercial and productive operations of said hacienda. The present case study entitled "Fulfillment of goals and objectives in the Audit Department of Hacienda Cooproclem" has been carried out with the purpose of raising awareness of the problems presented by said department at the time of carrying out its activities. daily, the inconveniences that arise between other circumstances that will be described in the development of the case both its causes and consequences and how it ends